1997
DOI: 10.1093/brain/120.5.739
|View full text |Cite
|
Sign up to set email alerts
|

Phonological and orthographic components of word recognition. A PET- rCBF study

Abstract: Pronunciation (of irregular/inconsistent words and of pseudowords) and lexical decision-making tasks were used with 15O PET to examine the neural correlates of phonological and orthographic processing in 14 healthy right-handed men (aged 18-40 years). Relative to a visual-fixation control task, all four experimental tasks elicited a left-lateralized stream of activation involving the lingual and fusiform gyri, perirolandic cortex, thalamus and anterior cingulate. Both pronunciation tasks activated the left sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
259
3
5

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(311 citation statements)
references
References 12 publications
44
259
3
5
Order By: Relevance
“…Furthermore, the posterior frontal group accounted for most of this deficit, and they were more aphasic than the anterior frontals. Their group averaged lesion included substantial overlap with the left inferior and middle frontal and left insular areas activated in the studies of Price et al w x w x 56 and Rumsey et al 64 , as illustrated in Fig. 1.…”
Section: Lexical-semantic Processing and Left Prefrontal Cortexmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the posterior frontal group accounted for most of this deficit, and they were more aphasic than the anterior frontals. Their group averaged lesion included substantial overlap with the left inferior and middle frontal and left insular areas activated in the studies of Price et al w x w x 56 and Rumsey et al 64 , as illustrated in Fig. 1.…”
Section: Lexical-semantic Processing and Left Prefrontal Cortexmentioning
confidence: 88%
“…These results will also be related to the neuroimaging literature. 56,64 , leading the former authors to conclude that the subjects adopted a phonological strategy to perform the task.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for an involvement of these areas in phonological processing is provided by a number of studies (e.g., Fiebach et al, 2002;Mechelli et al, 2007;Rumsey et al, 1997;Carreiras, Mechelli, and Price, 2006;Carreiras et al, 2007;Owen et al, 2004;Posner and Raichle, 1994;Ischebeck et al, 2004;Dietz et al, 2005, Borowsky et al, 2006 and also from imaging studies using pseudohomophones in visual word recognition reporting left and right inferior frontal gyrus activity (pars opercularis and triangularis) for pseudohomophones when compared to pseudowords (e.g., Edwards et al, 2005;Kronbichler et al, 2007).…”
Section: Early Phonological Activation In Visual Word Recognitionmentioning
confidence: 93%
“…This deficit has been associated with a dysfunction of the left ventral occipitotemporal cortex in adolescents and adults (e.g., (Brunswick et al, 1999;Helenius et al, 1999;Horwitz et al, 1998; Kronbichler et al, 2006; McCrory et al, 2005; Paulesu et al, 2001;Rumsey et al, 1997a;Rumsey et al, 1997b;Salmelin et al, 1996;Shaywitz et al, 2003; In our previous fMRI study, we specifically investigated print processing in the VWF-System in children with and without dyslexia while they indicated if visual stimuli (real words, pseudohomophones, pseudowords and false-fonts) sounded like a real word (Van der Mark et al, 2009). We found that a posterior-anterior gradient of print specificity (higher anterior activity to letter strings but higher posterior activity to false-fonts) as well as a constant sensitivity to orthographic familiarity (higher activity for unfamiliar than familiar word-forms) along the VWF-System could only be detected in controls.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…This deficit has been associated with a dysfunction of the left ventral occipitotemporal cortex in adolescents and adults (e.g., (Brunswick et al, 1999;Helenius et al, 1999;Horwitz et al, 1998;Kronbichler et al, 2006;McCrory et al, 2005;Paulesu et al, 2001;Rumsey et al, 1997a;Rumsey et al, 1997b;Salmelin et al, 1996;Shaywitz et al, 2003; as well as in children with dyslexia (e.g. (Cao et al, 2006;Hoeft et al, 2007;Maurer et al, 2007;Shaywitz et al, 2002;Shaywitz et al, 2007;van der Mark et al, 2009) for a large number of languages using a wide range of functional imaging methods.…”
mentioning
confidence: 99%